1981
DOI: 10.1016/s0006-3495(81)84842-4
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport across glycerol monooleate bilayer lipid membranes facilitated by magnesium etiochlorin

Abstract: The transport of electrons across biological membranes is believed to play an important role in many biophenomena. Although there have been many examples of systems which may be transporting electrons across Mueller-Rudin bilayer lipid membranes (blm), none has been well characterized. The system we describe here comprises a glycerol monooleate blm containing a magnesium etiochlorin (Mg-C) separating two aqueous phases each containing ferricyanide, ferrocyanide, KCl, and a platinum electrode. The E0s for the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…According to the VB method applied to redox DMPC vesicles (Figure S4), we can affirm that vesicles irreversibly adsorb onto the Pt UME, but the VR technique presented in Figure 3 clearly demonstrated that electron transfer does not occur through the BLM because electron tunneling and ion transfer is not facile through such a thick barrier. 19,20,31 Thus, in agreement with previous studies about the vesicle adsorption on various substrates, 12,13 DMPC vesicles seem to remain intact during their collision on the Pt UME hydrophilic surface.…”
Section: Resultssupporting
confidence: 90%
“…According to the VB method applied to redox DMPC vesicles (Figure S4), we can affirm that vesicles irreversibly adsorb onto the Pt UME, but the VR technique presented in Figure 3 clearly demonstrated that electron transfer does not occur through the BLM because electron tunneling and ion transfer is not facile through such a thick barrier. 19,20,31 Thus, in agreement with previous studies about the vesicle adsorption on various substrates, 12,13 DMPC vesicles seem to remain intact during their collision on the Pt UME hydrophilic surface.…”
Section: Resultssupporting
confidence: 90%
“…The same reaction is also suggested by Tien and Joshi [225] for PET across ZnTPP-containing planar BLM. Feldberg et al [226] also came to the conclusion about the existence of the transmembrane electron transfer via exchange reactions of the type of (8), when they found a square dependence of the membrane electrical conductivity on the concentration of the membrane-bound porphyrin (ethiochlorin of Mg(II)).…”
Section: Porphyrin-containing Membranesmentioning
confidence: 99%
“…Electron transport across lipid membranes is a fundamental property of living systems and is exemplified in photosynthesis. The designs of molecular systems for solar energy conversion are mimics of this vectorial photoinduced charge transportation. , However, relatively few synthetic molecules have been shown to transport charge across a lipid bilayer efficiently. With the recent success in producing macroscopic quantities of C 60 and C 70 fullerene molecules, many properties of these supermolecules have been determined. Since the photophysics of fullerene molecules resembles that of porphyrins and the fullerenes have low reduction potentials, , they are expected to have interesting charge-transfer chemistry in both the ground state and the excited states.…”
Section: Introductionmentioning
confidence: 99%